The Advancement of Islamic Financial Systems in Indonesia and Malaysia through the Use of Financial Technology as an Indicator: A Literature Study - Raihan Arlingga Pratama; Ramli nor Azuana (Journal of International Islamic Business Studies, 2025)
Abstract The rapid expansion of financial technology (fintech) has increasingly reshaped contemporary financial systems, including Islamic finance, where technological integration is no longer viewed merely as a service enhancement but as a systemic development affecting governance quality, operational efficiency, and Sharia compliance. Hasan et al. (2020) emphasize that “Fintech based solutions have the potential to improve transparency, accountability, and operational efficiency in Islamic finance,” while Alshater et al. (2022) point out that weaknesses in regulation and financial literacy remain significant obstacles to the growth of Islamic fintech. This study seeks to examine the advancement of Islamic financial systems in Indonesia and Malaysia by treating Islamic fintech as an indicative measure rather than as an independent analytical variable. Employing a qualitative literature review approach, the Islamic financial system at the national level is used as the unit of analysis. The comparative discussion focuses on three key dimensions: regulatory framework, institutional arrangement, and innovation dynamics. The results suggest that Malaysia demonstrates a more advanced level of Islamic financial system maturity, as reflected in its coherent regulatory structure and well-established Sharia institutions. In contrast, Indonesia shows substantial growth potential but continues to encounter challenges related to regulatory fragmentation and institutional coordination. Overall, this study argues that Islamic fintech can serve as a meaningful indicator for assessing the relative advancement of a country’s Islamic financial system. Keywords: Islamic fintech, Islamic financial system, Indonesia, Malaysia.